Effect of Different Partial Pressures on H2 Production with Parageobacillus thermoglucosidasius DSM 6285 - Magda Stephania Ardila; Habibu Aliyu; Pieter de Maayer; Anke Neumann (Fermentation)
The ability of Parageobacillus thermoglucosidasius to produce H2 from CO via the water–gas shift (WGS) reaction makes it a compelling microorganism for biofuels research. Optimizing this process requires evaluating parameters such as pressure. This study aimed to understand how H2 production is affected by increasing CO, N2, and H2 partial pressures to 1.0, 2.0, and 3.0 bar. Increasing CO partial pressure can improve the solubility of the gas in the liquid phase. However, raising CO partial pressure to 3.0 bar had an inhibitory effect, delaying and reducing H2 production. By contrast, increasing N2 and H2 partial pressures to 3.0 bar had positive effects, reaching a H2 production of 9.2 mmol and 130 mmol, respectively. Analysis of the electron balance at the end of the fermentation process showed that the selectivity toward H2 production reached 95%, with the remainder of electrons deriving from CO and glucose directed at organic acid production, mainly acetate, followed by formate.